2023
DOI: 10.1108/whatt-02-2023-0021
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability in hospitality education: research trends and future directions

Abstract: PurposeEducation for Sustainable Development (ESD) is a method intended to create awareness, knowledge, competence and attitude amongst stakeholders towards Sustainable Development Goals (SDGs) through higher education curricula. This bibliometric analysis, coupled with a systematic review, presents a comprehensive and objective assessment of the evolution of Sustainability in Hospitality Education (SHE) literature.Design/methodology/approachThis study integrated two review techniques: a systematic review and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…As such, teachers need to professionally take up opportunities that provide upskilling in Green Accounting in their workplaces, ensuring that they are more confident and aware of the debates and developments regarding environmental accounting. UNESCO (2005a) advocates for the participatory approaches to course design because once all the stakeholders contribute collectively at the design stage, it will bring into the picture the issue of ownership by those entrusted with implementing the planned curriculum (Piramanayagam et al, 2023). These ensure that there is a bridging of the gap between the planned and the implemented curricula.…”
Section: Green Accounting Attempts To Respond To the Challenges Of Co...mentioning
confidence: 99%
“…As such, teachers need to professionally take up opportunities that provide upskilling in Green Accounting in their workplaces, ensuring that they are more confident and aware of the debates and developments regarding environmental accounting. UNESCO (2005a) advocates for the participatory approaches to course design because once all the stakeholders contribute collectively at the design stage, it will bring into the picture the issue of ownership by those entrusted with implementing the planned curriculum (Piramanayagam et al, 2023). These ensure that there is a bridging of the gap between the planned and the implemented curricula.…”
Section: Green Accounting Attempts To Respond To the Challenges Of Co...mentioning
confidence: 99%
“…They indicated that renewable energy sources have benefits such as energy security, access, and economic and social development. Recently, the concept was applied in specific domains such as hospitality education 34 higher education, 35 aquaculture, 36 etc. using bibliometric analysis and systematic review approach with data from Scopus.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Piramanayagam et al, explored the research landscape and themes in sustainable hospitality education. 37 It was discovered that sustainable hospitality education was more skewed toward developed countries and was scarce in developing counties. Leal Filho et al examined the opportunities, benets, and challenges of internationalising universities from the sustainability perspective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…If the paper from Piramanayagam et al . (2023) is anything to go by, the answer to this question is a resounding “no”.…”
Section: Has Research In the Domain Of Sustainability Received Academ...mentioning
confidence: 99%